Product Lifetimes: The Current Research Landscape - Laursen, Linda Nhu; Hansen, Andreas Kornmaaler; de Götzen, Amalia; Dalhammer, Carl; Maitre-Ekern, Eleonore; Wieser, Harald; Grimstad Klepp, Ingun; Maldini, Irene; Ordóñez, Isabel; Richter, Jessika; et al. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This is the editorial for PLATE 2025